The Pitfall of Child Marriage Dispensation: A Study of Court Judgments in East Java (Dispensasi Perkawinan Anak yang Menjerumuskan: Studi Putusan Hakim di Jawa Timur) - Fajriyah, Iklilah Muzayyanah Dini; Marhamah, Siti; Anggriani, Septiani (UI Scholars Hub, 2023)
This article conducted study on court decisions on dispensation for marriage that occurred during the COVID-19 pandemic (June 2020 to February 2021) from the children’s rights perspective. The library research method was chosen to dissect 19 marriage dispensation decisions (12 decisions from religious courts and seven decisions from district courts) in Kraksaan and Sumenep districts, East Java. Child married couples were randomly selected with one or both parties under the age of 18. Three important findings in this study are: 1) the perspective of the best interests of the child has not been the main consideration for judges; 2) judges position girls as adults, standardize biased gender roles, and ignore children's experiences and aspirations; and 3) method of analysis that is not appropriate in measuring the meaning of a child's readiness to enter into marriage; neglect of children's basic rights, including education, reproductive health, and child development, as well as cultural bias makes the Marriage Dispensation Decision in this study a decision that is not in line with the prevailing laws on children’s rights.